Agility and quality attributes in open source software projects release practices - Silva, A. C. B. G. da.; Carneiro, G. de F.; Paula, A. C. M. de.; Monteiro, M. P.; Abreu, F. B. e. (2016 10th International Conference on the Quality of Information and Communications Technology (QUATIC), 2016)
Context: The need to accelerate software delivery, supporting faster time-to-market and frequent community developers/ users feedback are issues that have lead to relevant changes in software development practices. Many Open Source Software (OSS) projects have engaged to achieve this through the adoption of agile practices in software release practices. Problem: There is no secondary study in the literature discussing evidences of the influence of agile approaches in OSS projects release practices. Goal: Identify published reports in the literature that characterize to which extent agility has influenced release approaches in OSS projects. Method: The characterization of studies followed a fivephase process to present a panoramic view of software releases practices in the context of OSS projects. Results: The overall data collected from 14 studies published from January 2006 to January 2016 depicted the following scenario: nine issues that characterize the advantages/influence of agility in OSS release approaches; four challenge issues in this approach; three possibilities of implementation and two main motivations towards the adoption of software release approaches through agility; and finally three main strategies to implement it. Conclusion: This study provides an up-to-date and structured understanding of the influence of agility on OSS projects release approaches based on findings systematically collected from a list of relevant references in the last decade.